Clinical experience with temsirolimus in the treatment of advanced renal cell carcinoma. (June 2015) - Zanardi, Elisa; Verzoni, Elena; Grassi, Paolo; Necchi, Andrea; Giannatempo, Patrizia; Raggi, Daniele; De Braud, Filippo; Procopio, Giuseppe
Temsirolimus is an inhibitor of the mammalian target of rapamycin (mTOR) kinase, a protein that has been shown to be particularly active in metastatic renal cell carcinoma (mRCC) with poor prognosis. Therefore, temsirolimus should be considered as the first-line treatment indicated in mRCC patients classified as poor risk. The benefits of temsirolimus are not limited to an increased survival but are also related to a better quality of life, which is certainly one of the most important aspects in the clinical management of these frail patients. Temsirolimus is a well-tolerated treatment, and the most frequent adverse events are manageable with supportive care. To this end, the identification of predictive factors of response to temsirolimus could help us to better select patients and obtain a more tailored clinical management of mRCC.